2015
DOI: 10.1111/tmi.12503
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of maternal health services among adolescent women in Bangladesh: A scoping review of the literature

Abstract: Abstractobjective To understand the health-seeking behaviour of adolescent women in Bangladesh with respect to the use of maternal health services. results Twelve studies were included in this review. 11 used quantitative methods and one used a mixed-methods approach. All studies included married adolescent women only. Women with lower educational levels are less likely to seek skilled maternal health services than those with higher levels of education. Use of maternal health services is also less common among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 35 publications
(61 reference statements)
7
47
0
Order By: Relevance
“…husbands) restricted married adolescent girls’ autonomy towards making decisions of their own health care. Furthermore, girls with low levels of education had limited knowledge about reproductive health including the importance of the skilled maternal health care, a finding which has also been corroborated in other studies [29,35]. In addition, adolescent girls often were timid to communicate with husbands and other family members because of their culturally-grounded gender-role leading to limited level of autonomy [25,31,36].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…husbands) restricted married adolescent girls’ autonomy towards making decisions of their own health care. Furthermore, girls with low levels of education had limited knowledge about reproductive health including the importance of the skilled maternal health care, a finding which has also been corroborated in other studies [29,35]. In addition, adolescent girls often were timid to communicate with husbands and other family members because of their culturally-grounded gender-role leading to limited level of autonomy [25,31,36].…”
Section: Discussionmentioning
confidence: 65%
“…This huge proportion of child marriage contributes to the high rates of pregnancies among adolescent girls in Bangladesh. Existing literature indicates that women’s age, level of education, place of residence, decision-making autonomy, socio-cultural practices and norms, health beliefs and access and availability of quality health services influence the use of skilled maternal health services among women, including adolescents in Bangladesh [2229]. …”
Section: Introductionmentioning
confidence: 99%
“…However, without the empowerment of women, knowledge extension might be only half a battle won. Higher autonomy is reflected in the ability of women to decide whether to attend ANC clinics and makes it more likely for women to utilize the services (20,54). Our study showed that having decision-making power or autonomy to visit relatives might be associated with high first trimester registration and utilization of ANC services.…”
Section: Strengths and Limitationsmentioning
confidence: 69%
“…The components of ANC include risk identification, prevention and management of pregnancyrelated or concurrent diseases, nutritional problems, and health education and health promotion (19). Access to these services enables skilled health care professionals to identify and treat potential health risks to expecting woman and the unborn baby and ensures safe delivery (20).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the determinants of ANC use among youth has been influenced by predisposing, enabling, environment, need and health provider factors, although the influence is mixed. Antenatal care use has been associated with age of the youth (40), education level (25,40,41), pregnancy desire (42,43), and parity (25,40,44). Wealth quintile (26,30,45), employment status (46), region of residence (47)(48)(49) and urban residence were also associated with early and frequent ANC use (40,41).…”
mentioning
confidence: 99%